Digital culture and anxiety among generation z: the mediating role of social media addiction - Suhaimi Suhaimi; M. Fahli Zatrahadi (RedWhite Press, 2024)
Digital culture now shapes how Generation Z communicates, studies, and manages everyday relationships, and concern about its psychological cost has grown alongside it. This study asks whether digital culture raises anxiety among Islamic Guidance and Counseling (BKI) students, and whether social media addiction accounts for part of that relationship. Working from Uses and Gratifications Theory, Media Dependency Theory, Social Comparison Theory, and a cognitive-behavioral perspective, we tested a mediation model with 220 BKI students (59.5% female; most aged 21 to 23) at Universitas Islam Negeri Sultan Syarif Kasim Riau, Indonesia. Participants completed a 45-item Likert questionnaire (15 items per construct) delivered online over four weeks. Analysis used partial least squares structural equation modeling (PLS-SEM) in SmartPLS 4, and the indirect effect was estimated through bias-corrected bootstrapping with 5,000 subsamples. The measurement model met all reliability and validity criteria, and the structural model fit the data well (SRMR = 0.052). Digital culture predicted social media addiction (β = 0.650, 95% CI [0.556, 0.744], f² = 0.735) and anxiety (β = 0.298, CI [0.174, 0.422]). Social media addiction predicted anxiety (β = 0.462, CI [0.342, 0.582]) and partially mediated the digital culture–anxiety link (indirect β = 0.300, CI [0.212, 0.388]), carrying about half of the total effect (50.3%). The model explained 42.3% of the variance in social media addiction and 51.8% in anxiety. For Islamic counseling, the pattern argues for interventions that address the cultural pressures behind compulsive use, not symptoms alone, with the principle of wasatiyyah (moderation) offering a culturally grounded frame for that work.